A maternidade na Casa de Estudantes da UFSM: desafios e conquistas das acadêmicas mães moradoras da CEU - Pletiskaitz, Katiúcia (2018)
This research aimed at understanding how young academic mothers, living in the students’ residence, balance motherhood and academic formation at the Federal University of Santa Maria (UFSM, in Rio Grande do Sul, Brazil), and how this process impacts their access to public higher education. This study is part of the School Practice and Public Policy research line (LP2) of the Masters course in Education at the Federal University of Santa Maria. It was considered relevant to reflect and to discuss some aspects that have been proved important during this research, such as issues involving youth, gender issues, and maternity. To provide support to these discussions authors such as Mirla Cisne (2014a, 2004b, 2015), Heleieth Saffioti (2004), Pierre Bourdieu (2002), among others were studied. The research theme emerged from the concerns the author perceived while working as a Social Worker in Higher Education. This job was focused on the feasibility of public education policies, especially regarding the access and the stay of low-income students in public higher education. Another factor that contributed to the choosing of the researched subject was the interest in the research coordinated by Professor Sueli Salva, held in the students’ residence with mothers and their children. The present study was carried out with four young students living in the students’ residence of the UFSM. They balance their maternity and their academic formation in a space which was not planned for this. This is a qualitative research composed of autobiographical narratives, since this is the methodology considered to better bring out the aspects that are related to the daily life of these young student mothers. Data was produced through empirical research, bibliographical research, and interviews with young women, who composed their own autobiographical narratives and analysis. In these narratives the inequality of opportunities and the different levels of difficulties involved in public policies and in the academic formation of young mothers could be perceived. Issues considering the organization of time and routines that permeate youth, maternity, and the undergraduate life could also be observed.